Konsep Epitemologi Paradigma Thomas Khun - Nurkhalis Nurkhalis (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Thomas Kuhn describes that the science truth will be discovered many times from one object, although the method used changed. Formulation of paradigm theory sparks that the science truth (legitimated truth) is identical to teleology object, which is based on detection that is known as final cause. The truth science is not continuous, improvised, evolutioned, or cumulative. There is paradigm shift actually, which is known as revolution. Shifting paradigm is equally understood as gestalt switch, which discovers verification on all at once or not at all. Paradigm shift helps unfolding consciousness that scientists as unable to discover truth in objectively established manners. Paradigm designs the worldview’s frame or perspective to be more important, legitimate and reasonable. This led the detection to revolution or be eliminated due to its experimental ability in accommodating a new winnowing, which is discovered. Sustained paradigm will influence normal science as long as anomaly does not exist. The criteria of new paradigm are neater, more suitable, simpler, and more elegant.